Avaliação dos efeitos genotóxicos dos corpos de água temporários de um perímetro irrigado do semiárido sergipano, por meio do Teste SMART em Drosophila melanogaster (MEIGEN, 1830) e do teste do micronúcleo em anfíbios de Hypsiboas creptans (WIED-NEUWIED, 1824) - Santos, Poliana (2014)
In an attempt to solve the drought problem which causes the loss of agricultural productivity in the Brazilian semiarid zone, leading to starvation, unemployment and rural exodus, the Federal Government has deployed several public irrigated perimeters. In the State of Sergipe, we highlight the Irrigated California Area, which was intended to be the model of rational exploitation of soil and water in the northeast semi-arid. The main crops grown in this perimeter are acerola, banana, guava, mango, soursop, pumpkin, cassava, peanut, cowpea, maize, okra and tomato, with an average annual production of 12,682, 34 tons. Aiming to fulfill this agricultural demand, the use of pesticides and fertilizers is given in excess and without any technical support. This Perimeter is located in the surroundings of the Monumento Natural Grota do Angico a conservation unit. The excessive use of pesticides in this region can contaminate the environment, cause serious harm to human health, putting endangered the local wild species and those that inhabit the conservation area, can cause the loss of biodiversity and as a last destination can reach the water bodies near the plantations. Based on these data, we aimed in the present study to investigate the presence of pesticides with mutagenic effects in temporary water bodies in the Irrigated California Area by 2 tests: the SMART in the wings of D. melanogaster, in which the larvae were treated with water samples from 6 different points and the Micronucleus test, applied in erythrocytes of Hypsiboas creptans tadpoles collected in 3 water bodies between 2013 and 2014. The micronucleus test showed significantly higher frequency of micronuclei in tadpoles collected in one of the temporary water bodies in the Irrigated California Area (CD2) than the ones in the reference area (MNGA). In SMART Test we observed an increase in the frequency of mutant spot cells in the wings of D. melanogaster only in one of the water bodies (CD5), the one with no pesticides detected. The data presented here are pioneers in the evaluation of pesticides mutagenic effect in the semiarid irrigation areas of Sergipe and allow us to conclude that there are different sources of genotoxins presented in the Irrigated California Area, impacting the water and the resident biota, bringing huge risk for farmers and their families who live in that environment.